Acute exercise mobilizes CD8+ cytotoxic T cells and NK cells in lymphoma patients - Koivula, Tiia; Lempiäinen, Salla; Rinne, Petteri; Hollmén, Maija; Sundberg, Carl Johan; Rundqvist, Helene; Minn, Heikki; Heinonen, Ilkka (Frontiers in Physiology, 2023)
Background Studies have shown that acute exercise can mobilize several leukocyte subpopulations in healthy individuals. Our aim was to investigate whether a 10-minute acute exercise has an effect on immune cell proportions in lymphoma patients. Methods This study included seven lymphoma patients referred to curative oncologic therapy. Three had Hodgkin and four non-Hodgkin lymphoma, one was female, and their mean age was 51. Patients underwent a 10-minute acute exercise on a bicycle ergometer at moderate exercise intensity. Whole blood samples were taken at rest, immediately after exercise, and 30 minutes after exercise. Leukocyte subpopulation levels were determined using flow cytometry. Results Proportions of total NK cells and CD56+CD16+ NK cells of total leukocytes increased immediately after exercise and decreased back to baseline at 30 minutes post-exercise. Proportion of CD8+ T cells of total T cells increased and proportion of CD4+ T cells of total T cells decreased immediately after exercise, and both returned to baseline at 30 minutes post-exercise. There was no change in the proportions of B cells, granulocytes, or monocytes. Exercising diastolic blood pressure correlated positively with changes in total NK cell and CD56+CD16+ NK cell proportions, and exercising mean arterial pressure correlated positively with change in CD56+CD16+ NK cell proportion. Conclusion Our findings indicate that a single acute exercise bout of only 10 minutes can cause leukocytosis in lymphoma patients, particularly on cytotoxic T cells and NK cells, which are the most important immune cells fighting against cancer.